UNLOCKING CREATIVITY THROUGH COMICS ENHANCING STORY RETELLING SKILLS AMONG ISLAMIC UNIVERSITY STUDENTS USING ENGLISH COMICS - Mukhlisin (Suluh Adiluhung Publisher (SAPub), 2025)
This study explores the use of English comics as a tool to enhance story retelling skills among Islamic university students. The research employs a mixed-methods approach, combining quantitative and qualitative data to assess the effectiveness of comics in improving students' language proficiency. Sixty undergraduate students from an Islamic university participated in the study, with 30 students in the experimental group using English comics and 30 students in the control group following traditional text-based methods. Results revealed that the experimental group exhibited a significant improvement in their story retelling skills, as measured by pre-test and post-test assessments. The use of comics fostered higher engagement, creativity, and motivation, with students reporting that the visual and textual elements of comics facilitated better comprehension and narrative recall. Observations and interviews further highlighted the positive impact of comics on students' participation and their ability to construct coherent, creative retellings. This study underscores the cognitive and affective benefits of comics as a multimodal learning tool, providing valuable insights for educators seeking innovative methods to enhance language learning. The findings suggest that integrating comics into language curricula can significantly improve language skills, particularly in the areas of storytelling and narrative construction, while offering an engaging and culturally relevant learning experience. Future research is encouraged to explore the long-term effects and broader applications of comics in language education.